Mistrust and Beliefs in Conspiracy Theories Differently Mediate the Effects of Psychological Factors on Propensity for COVID-19 Vaccine - Simione, Luca; Vagni, Monia; Gnagnarella, Camilla; Bersani, Giuseppe; Pajardi, Daniela (Frontiers in Psychology, 2021)
Vaccination is considered a key factor in the sanitary resolution of the COVID-19 pandemic. However, vaccine hesitancy can undermine its diffusion with severe consequences on global health. While beliefs in conspiracy theories, mistrust in science, and mistrust in official information sources may also increment vaccine hesitancy, understanding their psychological causes could improve our capacity to respond to the pandemic. Thus, we designed a cross-sectional study with the aim of probing vaccine propensity in the Italian population and explore its relationship with socio-demographic and psychological variables, and with misbeliefs about COVID-19. A battery of questionnaires was administered to a sample of 374 Italian adults during the first national lockdown (April 2020). The materials included an original instrument – Beliefs in COVID-19 inventory – and questionnaires measuring perceived stress, anxiety, death anxiety, psychological distress, psychoticism, paranoia, anger, and somatization. The exploratory factor analysis on Beliefs in COVID-19 suggested the existence of three factors: Belief in conspiracy theories, Mistrust in medical information, and Mistrust in medicine and science. These factors were positively correlated to each other and with psychological symptoms. We then conducted a mediation analysis by means of a structural equation model including psychological factors as predictors, Beliefs in COVID-19 factors as mediators, and vaccine propensity as outcome. The model showed that death anxiety had a direct positive effect on propensity to get vaccinated, but it also reduced the propensity to get vaccinated through a mediated path in believing in conspiracy theories. Paranoia was linked to a reduction in vaccination adherence with the mediation effect of mistrust in medical science. Psychological distress reduced vaccination propensity by increasing both conspiracy beliefs and mistrust. On the other hand, anxiety increased the propensity to get vaccinated through a decrease in both belief in conspiracy theories and mistrust in science. Our results suggest that psychological dimensions differentially relate to belief in conspiracy theories, to mistrust in science, and to propensity to get vaccinated. Based on this result, we propose an original interpretation on how conspiracy beliefs build on a paranoid and suspicious attitude. We also discuss possible clinical implications of treatment for such pathological beliefs.